2020
DOI: 10.1039/c9ra08513k
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the electric permittivity of honeycomb-like core–shell Ni/CuSiO3 composite nanospheres to enhance microwave absorption properties

Abstract: Controlling impedance matching and enhancing absorption properties are crucial for developing next-generation microwave absorbing materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The nanospheres with a shell thickness of about 30 nm significantly enhanced microwave absorption performance when composited with wax. The wax composite showed strong reflection loss of −39.5 dB at 9.6 GHz for the absorber thickness of 2.5 mm, having an effective absorbing bandwidth of 4.8 GHz (7.8–12.6 GHz) . Liu et al reported hierarchical hollow CuS@CoS 2 nanoboxes with double shells.…”
Section: Discussion Of Emi Shielding/microwave Absorption Of Various ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The nanospheres with a shell thickness of about 30 nm significantly enhanced microwave absorption performance when composited with wax. The wax composite showed strong reflection loss of −39.5 dB at 9.6 GHz for the absorber thickness of 2.5 mm, having an effective absorbing bandwidth of 4.8 GHz (7.8–12.6 GHz) . Liu et al reported hierarchical hollow CuS@CoS 2 nanoboxes with double shells.…”
Section: Discussion Of Emi Shielding/microwave Absorption Of Various ...mentioning
confidence: 99%
“…The wax composite showed strong reflection loss of −39.5 dB at 9.6 GHz for the absorber thickness of 2.5 mm, having an effective absorbing bandwidth of 4.8 GHz (7.8−12.6 GHz). 161 Liu et al reported hierarchical hollow CuS@CoS 2 nanoboxes with double shells. These unique nanostructures were designed by a template-assisted process inspired by Pearson's hard and soft acid−base (HSAB) principle.…”
Section: ■ Em Absorption In Compositesmentioning
confidence: 99%
“…447,448 The formation of the core@shell could be an efficient route for developing the chemical homogeneity, oxidation stability, surface modification, dispersibility, enhanced functionality of the shell and the formation of a hollow morphology through the controlled release of the core. 449–507 In view of this, several reports on binary and ternary nanocomposites are reviewed below to explore the role of the unique features of the core@shell morphology in EMI shielding applications.…”
Section: Core@shell Nanocompositesmentioning
confidence: 99%
“…472 Fe@SiO 2 , 473 CoNi@C, 474 FeCo@SiO 2 , 475 FeCo@TiO 2 , 475 FeCo@SiO 2 @TiO 2 (ref. 475) CNS@MnO 2 , 476 cotton-derived carbon fibers@nano Cu, 477 Co@CoO, 478 and Ni@CuSiO 3 , 479 have also been investigated for their electromagnetic interference shielding and microwave absorption performances.…”
Section: Core@shell Nanocompositesmentioning
confidence: 99%